2010
DOI: 10.1080/00036840802112315
|View full text |Cite
|
Sign up to set email alerts
|

Impact of financial reforms on efficiency of state-owned, private and foreign banks in Pakistan

Abstract: This article uses a unique bank level data from 1991 to 2000 and evaluates how financial reforms affect banking efficiency of domestic and foreign banks in Pakistan. The results suggest that banking efficiency falls during initial reform period when banks adjust to enhanced competition but increases in more advanced stages of reform. While in general foreign and private banks show superior efficiency and factor productivity than do state-owned banks, the relative performance of foreign banks worsens after the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
74
2
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(85 citation statements)
references
References 40 publications
8
74
2
1
Order By: Relevance
“…Burki and Niazi analyzed the impact of financial reforms on the efficiency of state, private and foreign banks of Pakistan by using data of 40 banks for the period 1991-2000 [114]. They found a positive impact on bank size, interest income to earning assets and loans to deposit ratio on estimated efficiency scores.…”
Section: Gross Advances To Total Deposit Ratiomentioning
confidence: 99%
“…Burki and Niazi analyzed the impact of financial reforms on the efficiency of state, private and foreign banks of Pakistan by using data of 40 banks for the period 1991-2000 [114]. They found a positive impact on bank size, interest income to earning assets and loans to deposit ratio on estimated efficiency scores.…”
Section: Gross Advances To Total Deposit Ratiomentioning
confidence: 99%
“…The majority of the empirical literature has focused on changes in the efficiency level of banks based on ownership type and have highlighted that domestic private and foreign owned banks outperform state-owned banks (Altunbas et al, 2001;Berger, 2007;Burki & Niazi, 2010;Demir et al, 2005;Fries & Taci, 2005). However Gerschenkron (1962) justified government ownership in strategic economic sectors such as banking, emphasising the necessity of financial services for economic growth in the absence of private participation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An expansion in economic activities with improvements in investor sentiments due to the establishment of long-lasting peace in the country 1 , getting access to agricultural land in rebel held areas and revival of livelihood activities in war affected areas provided the necessary ingredient for banking institutions to expand their services. Although the literature on banking efficiency shows how ownership structures of banks links with efficiency of the banking industry (Altunbas et al, 2001;Berger, 2007;Burki & Niazi, 2010;Das & Gosh, 2006;Demir et al, 2005;Fries & Taci, 2005;Ray & Das, 2010), too little attention has been paid to evaluating this relationship when the economy experiences a favourable economic shock such as post-conflict economic developments. Therefore the present study evaluates how the ownership type of banks matter in terms of efficiency when the economy moves into a higher growth path in a post-conflict era.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietrich and Wanzenried (2014) indicated that larger banks might grasp efficiency gains that are reflected in higher earnings because they work in non-competitive financial markets. Moreover, Burki and Niazi (2010) analyzed the effect of financial reforms on bank efficiency of state owned, private owned, and foreign owned banks in Pakistan. Their study on 40 banks in Pakistan during 1991-2000 revealed that there is a positive impact of banks size, interest income to earning assets ratio, and loans to deposit ratio on estimated efficiency scores.…”
Section: Macroeconomic Factors and Bank Efficiencymentioning
confidence: 99%